Process–property–structure relationship in miniaturized injection moulded polyoxymethylene samples. Issue 3 (30th March 2013) - Baldi, F.; Bongiorno, A.; Fassi, I.; Franceschini, A.; Pagano, C.; Riccò, T.; Surace, R.; Tescione, F.
<x xml:space="preserve">Abstract</x> Micro‐injection moulding is one of the key manufacturing technologies for thermoplastic polymeric materials for the mass production of high value miniaturized components. However, this process is not just a straightforward down scaling of the conventional injection moulding technique. Indeed, during the micro‐injection the polymer melt is forced to flow at high strain rates through very small channels in nonisothermal conditions; this can lead to complex microstructures and to parts with unexpected performances. In this work, the relationships among the processing conditions, the mechanical properties and the microstructural characteristics of polyoxymethylene miniaturized specimens obtained by injection moulding were investigated. The attention was focused on the influence of the process temperatures on the mechanical behavior, examined by uniaxial tensile tests, and on the microstructural characteristics of the specimens, examined by differential scanning calorimetry, wide‐angle X‐ray diffraction, polarized light microscopy, and dynamic‐mechanical thermal analysis. The results highlighted that material ductility in the miniaturized specimens is significantly affected by the mould temperature, because of the sample microstructure. Different degrees of orientation of polymer crystallites and different morphologies of the skin/core transition region were observed in dependence on the process temperatures. POLYM. ENG. SCI., 54:512–521, 2014. © 2013 Society of Plastics Engineers